2023
DOI: 10.3390/aerospace10090782
|View full text |Cite
|
Sign up to set email alerts
|

Power Balance Strategies in Steady-State Simulation of the Micro Gas Turbine Engine by Component-Coupled 3D CFD Method

Yibing Xu,
Lei Gao,
Ruizhe Cao
et al.

Abstract: Currently, an increasing number of designers have begun to pay attention to a new paradigm for evaluating the performance with full engine 3-dimensional computational fluid dynamics (3D CFD) simulations. Compared with the traditional component-based performance simulation method component-based performance simulation method (‘component-matched’ method), this novel ‘component-coupled’ method can evaluate the overall performance of the engine more physically and obtain more detailed flow field parameters simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Additionally, many researchers have studied aspects such as the control [26,27], combustion emissions [28,29], power simulation [30], and exhaust nozzles [31] of micro-turbojet engines. However, there have been fewer studies combining deep learning with thrust prediction for micro-turbojet engines.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, many researchers have studied aspects such as the control [26,27], combustion emissions [28,29], power simulation [30], and exhaust nozzles [31] of micro-turbojet engines. However, there have been fewer studies combining deep learning with thrust prediction for micro-turbojet engines.…”
Section: Introductionmentioning
confidence: 99%
“…This simulation approach has the advantage of using less computational resources and producing results quicker, thus enabling more efficient performance sweeping across different operating points. With the continuous improvement in computational hardware capabilities, the number of full-engine simulations has increased steadily in recent years, and this trend is projected to be ongoing [22][23][24]. For example, Xu et al [22] compared the predictions of 3D full engine simulation between the coupled and uncoupled schemes.…”
Section: Introductionmentioning
confidence: 99%
“…Arroyo et al [23] demonstrated a 360-azimuthal-degree large-eddy simulation of the DGEN-380 demonstrator engine including a fully integrated fan, compressor, and annular combustion chamber at take-off conditions. Xu et al [24] proposed a component-coupled approach with the power balance iteration technique for 3D full engine CFD simulations. They successfully demonstrated the robustness of the method not only for the co-working state but also for the windmill stage of the gas turbine engine.…”
Section: Introductionmentioning
confidence: 99%